Integrative Scenarios as a Way of Smoothing the Barrier Between School and University Mathematics - Lavrenov, Andrey (Computer Tools in Education, 2023)
The article discusses possibilities of integrating concepts of informatics and mathematics in order to repeat important ideas of a school mathematics course and, at the same time, to introduce new concepts into a university course. The proposed approach is based on the use of dynamic geometry tools, as well as the combination of geometric and analytical representations. The presentation of theoretical considerations is accompanied by their illustration using the example of studying the Least Squares Method.